2018
DOI: 10.1139/cjes-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Karstic spring wetlands of the Persepolis Basin, southwest Iran: unique sediment archives of Holocene environmental change and human impacts

Abstract: Palustrine carbonates are frequently found with active and dried karstic springs in the foothills of the mountains bordering the Persepolis Basin, southwest Iran. A combination of geological conditions favours their formation, including (i) the presence of karstic limestone aquifers in the limbs of anticlines cut through by fault systems; (ii) very gentle slopes from the spring resurgence point towards the centre of the alluvial plain, creating a flat waterlogged area; and (iii) a semiarid climate with marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…2). A recent publication by Djamali et al (2018) has shown that similar age inversions (too young ages) have also been reported from a palustrine carbonate facies in the western Persepolis basin. We have retained the ages provided by the samples Poz-Arj503, Poz-Arj614, and Poz-Arj671 because they are composed of in situ organic matter (gyttja to very fine grained peat) formed within the aquatic environments through biological processes.…”
Section: Coring Lithostratigraphy and Radiocarbon Datingsupporting
confidence: 66%
“…2). A recent publication by Djamali et al (2018) has shown that similar age inversions (too young ages) have also been reported from a palustrine carbonate facies in the western Persepolis basin. We have retained the ages provided by the samples Poz-Arj503, Poz-Arj614, and Poz-Arj671 because they are composed of in situ organic matter (gyttja to very fine grained peat) formed within the aquatic environments through biological processes.…”
Section: Coring Lithostratigraphy and Radiocarbon Datingsupporting
confidence: 66%
“…Despite the fact that groundwater-fed areas leave well-recognized evidence in the geological record, their importance in defining the type of habitat available to hominins and other elements of the fauna is rarely recognized (but see Barboni, 2014;Beverly et al, 2015;Cuthbert et al, 2017;Deocampo and Tactikos, 2010;Djamali et al, 2018;Reynolds et al, 2011). Yet, we have shown here that the occurrence of springs is not anecdotal in the African hominin and human record (Table 1).…”
Section: Why Are Springs Ecological Keystones?mentioning
confidence: 99%
“…The analogy with modern pond sediment suggests that the percentages of peat and plant debris decrease from the littoral macrophytic belt toward the central pond basin, where carbonate mud (lime) becomes the dominant sediment type. The carbonate mud is mostly chemically and biochemically precipitated from the spring waters saturated in bicarbonates (Ashjari & Raeisi, 2006; Djamali et al, 2018). Thus, the following facies succession appears to represent a gradient from the littoral macrophytic vegetation belt to the deep lake/pond deposits close to the spring resurgence point: Phragmites peat, fine‐grained peat/gyttja, carbonate bioclastic organic mud, organic carbonate mud, and carbonate mud.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Understanding such hydraulic work and its effects on natural hydrological evolution of this freshwater ecosystem is crucial for several reasons. First, springs and spring wetlands have played a significant role in the socioeconomic and cultural evolution of societies in the arid to semi‐arid lands of the Iranian plateau, not only as permanent freshwater sources but also as places of gathering for religious rituals (Boucharlat, 1979; Canepa, 2018; Djamali et al, 2018; Huff, 1972, 2014). Second, the pond is an inseparable architectural element in the Ardashir Palace complex and therefore an excellent case study to examine the extent and techniques of possible landscape modification by Sasanians.…”
Section: Introductionmentioning
confidence: 99%